Significações imaginárias sobre a formação continuada de professores - Brezolin, Caroline Ferreira (2015)
This work is the result of a master's research, developed in the course of Postgraduate in Education in the Federal University of Santa Maria, in the years 2013-2015, registered on Education, Knowledge and Professional Development line. This research is a qualitative approach and sets up as a case study, conducted from observations, conversations and semi-structured dialogue with four cooperating teachers who work at the Municipal School of Early Childhood Education Borges de Medeiros of Santa Maria, Rio Grande do Sul. To support this study on teacher‟s education I use authors as Nóvoa (2009) Ferry (2004), more specifically on continuing education Moreira (2002) and Imbernon (2010). Regarding the Social Imaginary field I bring Castoriadis (1982) and Oliveira (1997, 2006, 2010, 2012), other authors that help to explore this theory. The discussions I create in this dissertation are under the Social Imaginary view, which brings the idea that man is imaginary and imagination, so he has the ability to create new forms, in addition to the already established. In this case, this framework helps us to understand that the education model that currently prevails, may have another configuration and take other directions for the subjects involved. In this study I had as main objective: to understand what are the imaginary meanings of the teachers on continuing education that they organize. In summary, during the research, there was the expansion of the concept of continuing education because the collaborators consider the weekly pedagogical meetings and dialogues about school planning involvement with the university, mediators of education devices. The school performs an establishing movement in the continuing education by organizing their own training, showing that this is the best place for the continuing education of teachers to take place, because to the participants it is important to discuss issues and share knowledge that arise in the work context.